Oregano essential oil (Origanum vulgare) and ginger dried extract (zingiber officinale) as potential growth promoters in broilers - Shiva, Carlos (2012)
The effect of adding oregano (Origanum vulgare) essential oil and dry ginger (Zingiber officinale) in the diet on body weight gain, feed intake and feed conversion rate was evaluated in 624 male Cobb 500 broiler chicks randomly assigned into four treatments with four replicates of 39 chicks each. Intestine and liver samples from four broilers per treatment were collected at day 14 and two at day 42 after treatment to determine possible histological toxic alterations and to determine the intestinal histomorphometry of jejunum. The treatments were: APC, Bacitracin methylene disalicylate (1 kg/MT of feed) and colistine sulfate 8% (0.25 kg/MT); SPC, without growth promoter; AEO, oregano essential oil (1 kg /MT); and JD, dryy ginger (10 kg/MT). There was no statistical difference between groups in body weight gain, feed intake and feed conversion rate. Group AEO showed slightly larger villi but without statistical differences with other groups. All birds showed alterations in jejunum and liver. It is concluded that the use of AEO and JD as growth promoter did not improved productive performance probably due to the low health challenge.